Perception of Country Tourism on Tourism Quality in Lake Toba North Sumatera 2020 - Solahuddin Nasution; Samerdanta Sinulingga; Arwina Sufika (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The tourism industry as a foreign exchange earner for the non-oil and gas sector in Indonesia has contributed US $ 16.426 billion in 2018 or around 200 trillion rupiahs. North Sumatra Province is one of the government's priorities in the tourism sector, measured from the construction of Sisingamangaraja XII International Airport in Silangit, the establishment of the Lake Toba Super Priority National Tourism Strategic Area (KSPN). The current Ministry of Tourism has made significant reforms, namely changing the focus from quantity tourism to quality tourism. The development of tourism quality that is currently underway in the Lake Toba area is then measured from the perceptions of tourists who respond to the quality values they have received while in the tourist area of Lake Toba. The theory used in this research is the theory of tourism by Nare, and the theory of foreign tourists by Ghanem. Furthermore, the method used is the quantitative data analysis method. Based on the results of the study it was found that the Cronbach's Alpha value was 0.931> 0.60, so as the basis for decision making in the reliability test, it can be concluded that the data tested was reliable or consistent and reliable. Tourism actors involved in the research were also mostly tourism actors in 2004, so based on their answers it was found that there was a significant change in perceptions of foreign tourists, namely 0.931%.